Eculizumab for Thrombotic Microangiopathy Associated with Antibody-Mediated Rejection after ABO-Incompatible Kidney Transplantation. (28th December 2017) - Lanfranco, Luca; Joly, Melanie; Del Bello, Arnaud; Esposito, Laure; Cognard, Noelle; Perrin, Peggy; Moulin, Bruno; Kamar, Nassim; Caillard, Sophie
Abstract : Thrombotic microangiopathy is a form of antibody-mediated rejection (ABMR): it is the main complication of ABO-incompatible (ABOi) kidney transplantation (KT). Herein, we report on two cases of ABMR with biological and histological features of thrombotic microangiopathy (TMA) that were treated by eculizumab after ABOi KT. The first patient presented with features of TMA at postoperative day (POD) 13. Because of worsening biological parameters and no recovery of kidney function, despite seven sessions of immunoadsorption, a salvage therapy of eculizumab was started on POD 23. Kidney function slightly improved during the first 4 months after transplantation. Eculizumab was stopped at month 4. However, kidney function worsened progressively, leading to dialysis at month 13 after transplantation. The second patient presented with features of TMA at POD 1. In addition to immunoadsorption therapy, eculizumab was started on POD 6. Kidney function improved. Eculizumab was stopped on POD 64 and immunoadsorption sessions were stopped on POD 102. At the last follow-up (after 9 months), eGFR was at 43 mL/min/1.73 m 2 . Our case reports show the beneficial effect of eculizumab to treat ABMR after ABOi KT. However, it should be given early after diagnosing TMA associated with ABMR.